Hukum Dakwah Dalam Alquran; Mengkaji Makna Perintah Dakwah Dalam Perspektif Tafsir Maudhui - M. Syukri Ismail; Januri Januri (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
There is a lot of debate in the midst of Muslims, regarding whether da'wah is wājib kifāyah or wājib 'ain. As a result of the debate, many Muslims left da'wah and there was a lot of decline (weak faith, weak deeds, corrupted morals, conflicts and being oppressed). Therefore, researchers are motivated to study the law of da'wah in the interpretation of the Qur'an. The research method uses a qualitative approach, and data analysis uses the tafsīr maudhū'i method, and the data sources are books of interpretation. As a result of his research, there are two da'wah laws: wājib kifāyah, and wājib 'ain. Scholars who say the law of obligatory da'wah kifāyah are Al-Suyuti, Al-Qurtubi, and Al-Andalusi. Fardhu kifāyah is an obligation that is obligatory on some Muslims, if there is already a group that preaches, then the others fall. They postulate the sentence min functions lit tab'īd, meaning in part; Muslims do not have to preach all, but there must be jihād, war, scientific councils, pesantren; and not all Muslims are able to preach, because there are stupid people, and the laity. The scholars who say the law of da'wah is wājib 'ain (obligation for every Muslim), are Ibn Kathir, Al-Razi, Al-Sya'rawi, Al-Maraghi, Al-Baghaw,i and Ibn Al-‘Arabi, with the reason: the sentence min functions li At -tabyīn (explanatory for all); supported by the verse